FRI0259 In vitro induced regulatory t-cells can ameliorate severity of pristane induced lupus (PIL). (12th June 2018) - Jacobs, B.; Leiss, H.; Gessl, I.; Puchner, A.; Smolen, J.; Stummvoll, G.
Abstract : Background: Pristane induced lupus (PIL) is an established murine model of induced systemic lupus erythematosus (SLE). Mice develop specific autoantibodies and show symptoms of SLE including arthritis, glomerulonephritis and haemorrhagic pulmonary capillaritis. Objectives: To investigate the therapeutic effects of in vitro -induced regulatory T cells (iTreg) in the murine model of PIL. Methods: BALB/c mice were injected i.p. with 0.5 ml of pristane (PIL) or PBS (control). Naive CD4 + thymocytes were sorted and cultured and cell suspensions with >80% CD4 + FoxP3 + cells (iTreg) were injected i.v. (i) once when PIL was induced (5 × 10 6  iTreg (iTreg-single)) or (ii) every 4 weeks (1 × 10 6  iTreg, iTreg-rep). Mice were monitored for paw swelling and grip strength. After 8 months, histological analysis quantified cartilage degradation, number of osteoclasts, extent of inflammation and bone erosion. Glomerulonephritis and pneumonitis were quantified using the kidney biopsy score and a histomorphometric image analysis system; inflammatory tissue was analysed by tissue cytometry. Serum levels of auto-antibodies were measured by ELISA. Frequencies of B cells, activated and regulatory CD4 + T cells and Th1, Th2, Th17 cells were measured by flow cytometry. FlowCytomix Pro was used to measure serum cytokines. RT-qPCR was used to measure expression levels of interferon (IFN)-signature and T-cell subset related as well as inflammation-associated genes. Results: Monthly injections of 1 × 10 6  iTreg reduced the clinical and histological severity of PIL-arthritis. This was seen by a higher mean grip strength, less mean paw swelling, retardation of symptom onset and a lower summative arthritis severity score (figure A). There was significant reduction of arthritis severity in all histological parameters and in the percentage of affected mice with erosive arthritis (33% of iTreg-rep mice vs 62% of PIL-mice). A single boost of 5 × 10 6  iTreg could not prevent joint manifestation, however a slight retardation in 'loss of grip strength' and significantly less erosive area was seen. In regards to cellular composition of the inflammatory tissue in paws, a significantly increased relative amount of CD4 +Foxp3+cells was seen in the iTreg-rep group compared to PIL group. Repeatedly injected mice (iTreg-rep) had significantly less renal disease (glomerular activity score) (figure B) and pulmonary involvement (perivascular inflammatory area) (figure C) compared to PIL. iTreg-rep mice had significantly lower serum levels of disease-associated auto-antibodies (figure D). Upon restimulation, splenic CD4 + cells in iTreg-rep showed a less pronounced Th1, Th2 and Th17 response as well as lower percentages in B- and activated T-cells, whereas the percentage of Treg was higher than in all other groups (figure E). FlowCytomix analysis showed reduced cytokine production after repeated iTreg administration. Correspondingly, iTreg-rep showed decreased expressions of IFN-signature-, T-cell subset- and inflammatory cytokine related genes (figure F). Conclusions: Repeated injections of iTreg ameliorate the clinical, histological, serological as well as the genetic severity of PIL-manifestations. A single boost of iTreg at time of disease induction does not prevent manifestations, but retards the onset of symptoms. Thus iTreg have significant positive effects on PIL, which may have consequences for future approaches in treating SLE. Disclosure of Interest: None declared